Local release from affinity-based polymers increases urethral concentration of the stem cell chemokine CCL7 in rats. (21st April 2016) - Rivera-Delgado, Edgardo; Sadeghi, Zhina; Wang, Nick X; Kenyon, Jonathan; Satyanarayan, Sapna; Kavran, Michael; Flask, Chris; Hijaz, Adonis Z; von Recum, Horst A
Abstract: The protein chemokine (C-C motif) ligand 7 (CCL7) is significantly over-expressed in urethral and vaginal tissues immediately following vaginal distention in a rat model of stress urinary incontinence. Further evidence, in this scenario and other clinical scenarios, indicates CCL7 stimulates stem cell homing for regenerative repair. This CCL7 gradient is likely absent or compromised in the natural repair process of women who continue to suffer from SUI into advanced age. We evaluated the feasibility of locally providing this missing CCL7 gradient by means of an affinity-based implantable polymer. To engineer these polymers we screened the affinity of different proteoglycans, to use them as CCL7-binding hosts. We found heparin to be the strongest binding host for CCL7 with a 0.323 nM dissociation constant. Our experimental approach indicates conjugation of heparin to a polymer backbone (using either bovine serum albumin or poly (ethylene glycol) as the base polymer) can be used as a delivery system capable of providing sustained concentrations of CCL7 in a therapeutically useful range up to a month in vitro . With this approach we are able to detect, after polymer implantation, significant increase in CCL7 in the urethral tissue directly surrounding the polymer implants with only trace amounts of human CCL7 present in the blood of the animals. Whole animal serial sectioning shows evidence of retention of locally injected human mesenchymal stem cells (hMSCs) only in animals with sustained CCL7 delivery, 2 weeks after affinity-polymers were implanted.